FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU PERSONAL HYGIENE SAAT MENSTRUASI PADA SISWI SMK VETERAN CIREBON - Aprilikka Early Putrinda Suharyadi (2022)
Menstruation is a sign that girls are starting to go through puberty. If young women neglect reproductive hygiene during menstruation, many issues might arise, including infection with genital organ-specific pathogens. In Indonesia, there are 90-100 cases per 100,000 each year, with teens reporting the highest incidence. The purposeiof thisistudy is to determine the variables influencing female students at SMK Veteran Cirebon's personal hygiene practices during menstruation. At SMK Veteran Cirebon in 2022, a cross-sectional study of students in grades X, XII, and XII was conducted. Utilizing stratified random sampling, the sample was taken. Personal information, menarche age, knowledge of parents, socioeconomic level, parental support, and personal hygiene were all part of the questionnaire. According to the study's 63 respondents, 79.4% of the sample maintained personal hygiene while having their period. According to the study's findings according on the chi square test, the p value for the correlationibetween parental support and female students of SMK Veteran Cirebon's personal hygiene practices during menstruation was 0.018 0.05. It is clear from the study's findings that menstrual hygiene is significantly correlated with age of menarche, father's occupation, mother's occupation, level of knowledge, and socioeconomic status. This study is anticipated to serve as a reminder of the value of taking care of oneself and preserving reproductive health. Keywords: Personal hygiene, menstruation, and parental support